Correlation of circulatory VEGF and miRNA 126 in angiographically proven coronary artery disease and its clinical importance - Manzeela Swale,; Kushwaha, Neetu; Mohd Sajid Khan, (Asian Journal of Medical Sciences, 2024)
Background: Atherosclerotic ischemic coronary artery disease (CAD) is a major cause of morbidity and mortality in both developed and developing countries, indicating the need for the discovery of deeper molecular insights of CAD mechanisms, biomarkers, and innovative therapeutic targets. Vascular endothelial growth factor (VEGF) may have some role, in the progression of human coronary atherosclerosis. Circulating microRNAs (miR) have a potential as a diagnostic as well as a prognostic biomarker of cardiovascular disease and dysfunctions. Aims and Objectives: The aim of the study was to correlate the levels of miRNA-126 and VEGF in the serum of CAD patients. Materials and Methods: The study was conducted on 100 cases of freshly diagnosed CAD patients (angiographically proven) and 80 normal healthy patients. Various serum biomarkers were estimated. The level of serum VEGF and Mi-RNA was correlated for CAD patients. Results: Highly significantly difference was found in levels of hemoglobin A1C, low density lipoprotein, total cholesterol, and total homocysteine while high-density lipoproteins and triglycerides were less significantly different for controls and cases. VEGF levels of CAD cases were found to be very significantly higher as compared to controls. The miRNA-126 expression was found to be lower in the CAD subjects compared to non-CAD subjects. Conclusion: The study was suggested the role of VEGF in atherogenesis and plaque instability. No significant correlation was found among between miR-126 levels and VEGF levels among CAD cases. The study is limited by a smaller sample size and was single-centered; therefore, multicentric study with a larger patient cohort needs to be done and to validate our findings.